SISTEM PENDETEKSI JUMLAH MOBIL DALAM INTELLIGENT TRANSPORT SYSTEM (ITS) MENGGUNAKAN METODE VIOLA-JONES - Irmaya Citra Harwendhani; Ika Purwanti Ningrum; Muh. Ihsan Sarita (Informatics Engineering Department of Halu Oleo University, 2016)
One way to cope with the traffic density is leveraging technology Intelligent Transport System (ITS). ITS is a system implemented to control and manage the traffic of vehicles, vehicle distribution and transport system infrastructure to achieve a more secure and organized. Revolving a traffic light in the ITS is flexible because it depends on the number of vehicles in traffic. To obtain the revolving time efficient traffic light depends on the accuracy of the calculation of the number of vehicles. In this study, the method used is the method of viola-Jones. The number of car detection system is implemented using the Java programming language-based desktop. Results obtained from these systems demonstrate the highest degree of accuracy viola-Jones method in detecting the number of cars on the condition of the samples contained 1 cars which amounted to 92,86%. While the highest error jones viola method in determining the number of cars found on a random sample conditions which amounted to 47,22%.Keywords— ITS, Car Detection, Viola-Jones